SYMMETRIES IN ODD-MASS NUCLEI - Van Isacker, P. (HNPS Advances in Nuclear Physics, 2020)
A general review is given of applications of algebraic techniques to odd-mass nuclei in the framework of the interacting boson-fermion model. The discussion focuses on the symmetry aspect of the model: the concepts of symmetry and dynamical symmetry are illustrated by way of elementary examples. The unified treatment of even-even and odd-mass nuclei (supersym- metry) is introduced by inspecting the action of 'super'generators creating a boson and annihilating a fermion (or vice versa). These ideas are illustrated with some examples. The talk is concludes with a brief summary.